The paradoxical role of IL-10 in immunity and cancer. Issue 2 (28th October 2015) - Mannino, Mark H.; Zhu, Ziwen; Xiao, Huaping; Bai, Qian; Wakefield, Mark R.; Fang, Yujiang
Highlights The role of IL-10 in tumorigenesis and development is still controversial. One explanation is the balance of cytokines and other conditions delicately controlling its function in different cell types. It is also possible that IL-10 might play a dual role in tumorigenesis and development.